In situ characterization of local elastic properties of thin shape memory films by surface acoustic waves. (15th November 2016) - Grabec, Tomáš; Sedlák, Petr; Stoklasová, Pavla; Thomasová, Martina; Shilo, Doron; Kabla, Meni; Seiner, Hanuš; Landa, Michal
Abstract: The impulse stimulated thermal scattering experimental technique is used for contactless in situ detection of phase transitions in thin nickel-titanium films deposited on silicon substrates. It is shown that this technique enables the determination of the local properties of the film over a fully coated wafer, in particular the thickness of the film and the temperature dependence of the Young's modulus, and can thus be used for monitoring of the spatial distribution of the functional properties in films prepared by a combinatorial sputtering approach.